A Nanostructured Lipid System to Improve the Oral Bioavailability of Ruthenium(II) Complexes for the Treatment of Infections Caused by Mycobacterium tuberculosis - da Silva, Patricia B.; de Freitas, Eduardo Sinésio; Solcia, Mariana Cristina; de Souza, Paula Carolina; da Silva, Monize Martins; Batista, Alzir Azevedo; Eismann, Carlos E.; Rolisola, Ana Marta C. M.; Menegário, Amauri A.; Cardoso, Rosilene Fressatti; Chorilli, Marlus; Pavan, Fernando R. (Frontiers in Microbiology, 2018)
Tuberculosis (TB) is an infectious, airborne disease caused by the bacterium Mycobacterium tuberculosis that mainly affects the lungs. Fortunately, tuberculosis is a curable disease, and in recent years, death rates for this disease have decreased. However, the existence of antibiotic-resistant strains and the occurrence of co-infections with human immunodeficiency virus (HIV), have led to increased mortality in recent years. Another area of concern is that one-third of the world's population is currently infected with M. tuberculosis in its latent state, serving as a potential reservoir for active TB. In an effort to address the failure of current TB drugs, greater attention is being given to the importance of bioinorganic chemistry as an ally in new research into the development of anti-TB drugs. Ruthenium (Ru) is a chemical element that can mimic iron (Fe) in the body. In previous studies involving the following heteroleptic Ru complexes, [Ru(pic)(dppb)(bipy)]PF6 (SCAR1), [Ru(pic)(dppb)(Me-bipy)]PF6 (SCAR2), [Ru(pic)(dppb)(phen)]PF6 (SCAR4), cis-[Ru(pic)(dppe)2]PF6 (SCAR5), and [Ru(pic)(dppe)(phen)]PF6 (SCAR7), we observed excellent anti-TB activity, moderate cell-toxicity, and a lack of oral bioavailability in an in vivo model of these complexes. Therefore, the objective of this study was to evaluate the toxicity and oral bioavailability of these complexes by loading them into a nanostructured lipid system. The nanostructured lipid system was generated using different ratios of surfactant (soybean phosphatidylcholine, Eumulgin®, and sodium oleate), aqueous phase (phosphate buffer with a concentration of 1X and pH 7.4), and oil (cholesterol) to generate a system for the incorporation of Ru(II) compounds. The anti-TB activity of the compounds was determined using a microdilution assay with Resazurin (REMA) against strains of M. tuberculosis H37Rv and clinical isolates resistant. Cytotoxicity assay using J774.A1 cells (ATCC TIB-67) and intra-macrophage activity were performed. The oral bioavailability assay was used to analyze blood collected from female BALB/C mice. Plasma collected from the same mice was analyzed via inductively coupled plasma mass spectrometry (ICP-MS) to quantify the number of Ru ions. The complexes loaded into the nanostructured lipid system maintained in vitro activity and toxicity was found to be reduced compared with the compounds that were not loaded.